PERSEPSI DAN EKSPEKTASI WISATAWAN TERHADAP KOMPONEN DESTINASI WISATA LAKEY-HU’U, KABUPATEN DOMPU - Kurniansah, Rizal (Jurnal Master Pariwisata (JUMPA); Volume 03, Nomor 01, Juli 2016, 2016)
This study aims to determine the key components of tourism destinations Lakey-Hu’u, Sumbawa Island.It also examines the perceptions and expectations of tourists to the quality of the components, and describes the improvised program of the Lakey- Hu’u components.Data were collected through observation, interviews, and questionnaires which then analysed using theory component of the tourism product and the theory of perception.The results showed that the decisive component of tourism destinations Lakey-Hu’u include attractions, amenities, accessibility, ancillary, and community involvement.Based on the analysis of the Likert scale rating on the perceptions and expectations of the quality of tourism destinations Lakey-Hu’u component, the average rating was already good, improvisation program components that get listed on the main handling quadrant I, among others: a parking lot, a lifeguard, ding repair, the condition of transport modes to the location and completeness of the information through the Internet, travel agents, tour brochures or information.
Keywords: perception, expectations, tourists, Lakey-Hu’u tourism destinations